包公斷案中的冥界觀念探析 - 吳曉麗; Wu Xiaoli (중국학보, 2022)
“冥界”是人們對死後世界的想象, 冥界觀念的形成與中國傳統的民間信仰和宗教信仰有不可分割的聯繫。隨著佛教在中土的傳播, 民間信仰和佛教文化逐漸融合, 佛教的地獄觀念豐富了中國傳統的冥界觀念, 並出現於各種文學作品中, 遊冥故事成爲古典小說中一個重要的敍事類型。 明代各種文學體裁中都有遊冥情節登場, 尤其是通俗小說中出現冥判的頻率極高, 公案小說最爲明顯。包公系列的公案小說中作者賦予包公神判的能力, 將其描寫成一位日審陽間, 夜判陰間的判官, 突顯其秉公執法的形象。冥判情節的建構主要是爲了豐富小說的表現力, 實現小說懲惡揚善的功能。本文擬從包公案中描寫的冥判故事入手, 探析包公斷案過程中反映的冥界觀念, 主要從冥者的伸冤樣相和包公的冥判方式兩個方面進行探討, 並以此來管窺明代中後期民衆的宗教觀和生死觀。 The nether world is people’s imagination of the world after death. The formation of the concept of the nether world has an inseparable connection with the traditional Chinese folk beliefs and religious beliefs. With the spread of Buddhism in China, folk beliefs and Buddhist culture were integrated gradually. The Buddhist concept of hell enriched the traditional Chinese concept of the nether world, which appeared in various literary works. Ghost stories have become an important narrative genre in classical fiction. Ghost stories appeared in various literary genres in the Ming Dynasty, especially in popular fictions. The prosperity of crime-case fiction brought new opportunities for ghost stories. In Bao Gong’s series of crime-case fictions, the authors endowed Bao Gong with divine powers to try cases between this world and the nether world. This kind of plot was mainly to enrich the fiction’s expressive power and realize its admonition function. This paper explores two categories of the concept of the nether world through which to examine the common people’s views on religion and death of the middle to late Ming Dynasty: the way of ghosts’ appeal and the process of Bao Gong’s trials and verdicts.